2022
DOI: 10.5455/javar.2022.i632
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality and in vitro digestibility of fermented rice bran based on different types and doses of inoculants

Abstract: Objective: The study was conducted to determine the effect of inoculants of different types and doses on the nutrient quality and in vitro digestibility of fermented rice bran. Materials and Methods: The study was designed using a completely randomized design with a 3 × 3-factorial pattern. The first factor was the type of inoculum, consisting of Saccharomyces cerevi¬siae (SC), Effective Microorganism-4, and Saus Burger Pakan (SBP). The second factor is inoculum doses, which are as follows: levels 2%, 4%, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Crude fiber affects digestibility, so a good feed does not contain more than 8 percent crude fiber. Laboratory test results still show that the crude fiber content is quite high, which forms pores in the feed (Dilaga et al, 2022). This also affects the low buoyancy (floating).…”
Section: Test Results Do Not Meet Snimentioning
confidence: 99%
“…Crude fiber affects digestibility, so a good feed does not contain more than 8 percent crude fiber. Laboratory test results still show that the crude fiber content is quite high, which forms pores in the feed (Dilaga et al, 2022). This also affects the low buoyancy (floating).…”
Section: Test Results Do Not Meet Snimentioning
confidence: 99%
“…Cellulose, hemicellulose, lignin, and silica are the constituent components of ADF. Dilaga et al [ 23 ] explained that the low content of the ADF fraction obtained in their study was due to the ability of microbes to separate hemicellulose-lignin linking to making up the cell walls, and part of the hemicellulose was also degraded, causing the low content of the ADF fraction. However, the discussion regarding reducing the CF fraction in silage is still incomplete and needs further study.…”
Section: Discussionmentioning
confidence: 98%
“…The increased number of LAB causes their nutritional needs to increase [ 22 ]. Microorganisms need essential nutrients, especially energy sources, to support cell multiplication [ 23 ]. In the anaerobic fermentation process, fermented sugar is used in high amounts during the intensive fermentation phase during the aerobic respiration period, but when the fermentation process enters the stable phase, the demand for the substrate is reduced [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…They further explained that legumes in the feed provide a nitrogen source for rumen microbes. For rumen microbes, the availability of nitrogen, carbon, and ATP sources can encourage intensive cell multiplication (Dilaga et al, 2022). Another study by Xue et al (2020) under in vitro assessment showed that there was an increase in DMD and OMD of mixed silage of Orchardgrass and Alfalfa, which was caused by an increase of protein content and a decrease in the fiber fraction as the proportion of alfalfa was added.…”
Section: Rumen Fermentation Profilementioning
confidence: 99%